DEVELOPMENT AND IMPROVEMENT OF LEAD-COPPER CONCENTRATE SEPARATION TECHNOLOGY USING A LOCAL REAGENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Improvement of the technology of enrichment of polymetallic ores and methods of separation of collective concentrates can increase the share of production of copper, lead, zinc, rare and noble metals without excessive costs. In practice, separating the lead-copper collective concentrate from each other is one of the most difficult tasks facing enrichment technologists. In recent years, as a result of scientific research conducted by researchers on the extraction of lead-copper concentrates, it has been possible to reduce the copper content in the lead concentrate at many processing plants and increase the quality and extraction percentage of the lead concentrate.